Should Target Glucose Values Be Increased to Avoid Severe Hypoglycemia? Real-World Data Say “No.” - Welsh, John (J Endocr Soc, 2021)
Early studies such as the Diabetes Control and Complications Trial showed a strong inverse relationship between A1C and the risk of severe hypoglycemia in type 1 diabetes. This risk has historically limited insulin therapy intensification efforts, and some treatment guidelines (e.g., Rosenzweig et al., J Clin Endocrinol Metab 105:969, 2020) suggest that A1C values <7% confer an increased risk of hypoglycemia. Nowadays, real-time continuous glucose monitoring (CGM) systems can flatten and attenuate the relationship between overall glucose control and hypoglycemia (Oliver et al., Diabetes Care 43:53, 2020). The glucose management indicator (GMI) is an estimate of A1C derived from the CGM system’s mean estimated glucose value (EGV) (Bergenstal et al., Diabetes Care 41:2275, 2018). We analyzed real-world evidence of the relationship between the GMI and exposure to hypoglycemia. Data were from an anonymized convenience sample of US-based users of the G6 CGM system (Dexcom, Inc., San Diego, CA) who used a mobile device to upload EGVs in the third quarter of 2020. Only data from people who had uploaded ≥80% of possible values were included. Each person’s GMI was calculated as GMI = 3.31 + (0.02392 × mean EGV [mg/dL]). Each person’s exposure to hypoglycemia was estimated as the percentage of EGVs <70 mg/dL or <54 mg/dL (%<70 and %<54, respectively). Patients were grouped into 6 categories according to GMI values <6.5%, 6.5 to 6.9%, 7.0 to 7.4%, 7.5 to 7.9%, 8.0 to 8.4%, and ≥8.5%. Mean %<70 mg/dL and %<54 mg/dL were both inversely correlated with GMI, decreasing monotonically as the GMI category increased. GMI category, %<70, and %<54 are as follows: (<6.5%: 5.27%, 1.13%); (6.5 to 6.9%: 2.84%, 0.59%); (7.0 to 7.4%: 1.95%, 0.41%); (7.5 to 7.9%: 1.46%, 0.31%); (8.0 to 8.4%: 1.14%, 0.25%); (≥8.5%: 0.69%, 0.17%). However, in all GMI categories except for the “<6.5%” category, the extent of hypoglycemic exposure was below the consensus targets proposed by Battelino et al. (Diabetes Care 42:1593, 2019) of <4% for EGVs <70 mg/dL and <1% for EGVs <54 mg/dL. The approach of elevating A1C targets to reduce hypoglycemia risk is not supported by real-world evidence for CGM users who have GMI or A1C values ≥6.5%. CGM users can safely strive for A1C values <7.0%.